Особенности психотерапевтических и психообразовательных мероприятий с родственниками больных параноидной шизофренией = The features psychotherapeutical and psycho-educational activities with relatives of paranoid schizophrenia patients - K. V. Aymedov; A. V. Morvaniuk (Kazimierz Wielki University, 2015)
Aymedov K V, Morvaniuk A V. Особенности психотерапевтических и психообразовательных мероприятий с родственниками больных параноидной шизофренией = The features psychotherapeutical and psycho-educational activities with relatives of paranoid schizophrenia patients. Journal of Education, Health and Sport. 2015;5(5):131-137. ISSN 2391-8306. DOI 10.5281/zenodo.17464 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A131-137 https://pbn.nauka.gov.pl/works/559203 http://dx.doi.org/10.5281/zenodo.17464 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   УДК: 616.895.8-08:3 ОСОБЕННОСТИ ПСИХОТЕРАПЕВТИЧЕСКИХ И ПСИХООБРАЗОВАТЕЛЬНЫХ МЕРОПРИЯТИЙ С РОДСТВЕННИКАМИ БОЛЬНЫХ ПАРАНОИДНОЙ ШИЗОФРЕНИЕЙ THE FEATURES PSYCHOTHERAPEUTICAL AND PSYCHO-EDUCATIONAL ACTIVITIES WITH RELATIVES OF PARANOID SCHIZOPHRENIA PATIENTS   К. В. Аймедов, А. В. Морванюк K V Aymedov, A V Morvaniuk   Одесский национальный медицинский университет, Одесса Odessa National Medical University, Odessa   Abstract In the article the author gives an analysis of literary sources of native and foreign authors related to the approaches of psychocorrectional work with relatives of paranoid schizophrenia male and female patients. It is analyzed the main issues of behavioral family therapy and psychoeducational interventions that are an integral part of the assistance to families in which there is a patient with psychosis. Key words: paranoid schizophrenia, psychoeducation, family approach, psycho-pedagogical model.   Резюме В статье автор приводит анализ литературных источников отечественных и зарубежных авторов касающихся подходов к психокоррекционной работе с родственниками больных параноидной формой шизофрении мужчин и женщин. Проанализированы основные вопросы поведенческой семейной психотерапии и психообразовательных мероприятий, которые являются частью неотъемлемой помощи семье, в которой есть больной с психозом. Ключевые слова: параноидная шизофрения, психообразование, семейный подход, психо-педагогическая модель.